Doyle’s Diogenes Club: a Delightful Oddity Screening a Metatextual Clue - Nathalie Jaëck (Cahiers Victoriens et Edouardiens)
In this paper I propose to study Mycroft Holmes’s club in the Sherlock Holmes stories: the Diogenes Club is rather close to an oxymoron as the golden rule is that the members are not allowed to speak to one another. I will show how this textual detail, that eminently Doylian delicious paradox, can read as a rather elaborate parody of the ambivalence of Victorian clubs, where the ideal of sociability cohabits with a more dissident taste for secrecy and seclusion. It can also read as a metatextual clue to the strategic importance of silence in Conan Doyle’s text. That famous inquisitive text, a positivist celebration of the powers of logos, also makes room for a crucial vindication of silence, and creates the paradoxical possibility for the text to escape the very paradigms it powerfully establishes.